1988
DOI: 10.1113/jphysiol.1988.sp017217
|View full text |Cite
|
Sign up to set email alerts
|

Transport of L‐phenylalanine and related amino acids at the ovine blood‐brain barrier.

Abstract: SUMMARY1. Unidirectional influx ofamino acids at the blood-brain barrier was studied in the lamb and sheep under barbiturate anaesthesia using the single-pass indicatordilution technique.2. In the lamb, influx of both L-phenylalanine (14+1 nmol g-1 min-1) and Lalanine (12 + 2 nmol g-1 min-') was greater than in the sheep: L-phenylalanine influx, 9 + 1 nmol g-' min-'; L-alanine influx, 5 +1 nmol g-' min-' (P < 0-01). This difference reflected higher blood concentrations of these amino acids in the younger anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…In order to determine if a relationship exists between tyrosine levels and dopamine synthesis in the treated PKU mouse brain, it was necessary to quantify tyrosine in blood and brain tissues in control heterozygous, untreated PKU, and treated PKU mice. Based upon previous studies showing that high levels of Phe out‐compete tyrosine for transport across the blood–brain barrier (Choi and Pardridge 1986; Brenton and Gardiner 1988; Pardridge 1998), it was anticipated that brain tyrosine levels would be less than blood tyrosine levels in the untreated PKU mouse. However, we unexpectedly found that tyrosine levels in frontal cortex and striatum were approximately 1.2‐ and 1.4‐times, respectively, the level of tyrosine in the blood of untreated PKU mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to determine if a relationship exists between tyrosine levels and dopamine synthesis in the treated PKU mouse brain, it was necessary to quantify tyrosine in blood and brain tissues in control heterozygous, untreated PKU, and treated PKU mice. Based upon previous studies showing that high levels of Phe out‐compete tyrosine for transport across the blood–brain barrier (Choi and Pardridge 1986; Brenton and Gardiner 1988; Pardridge 1998), it was anticipated that brain tyrosine levels would be less than blood tyrosine levels in the untreated PKU mouse. However, we unexpectedly found that tyrosine levels in frontal cortex and striatum were approximately 1.2‐ and 1.4‐times, respectively, the level of tyrosine in the blood of untreated PKU mice.…”
Section: Discussionmentioning
confidence: 99%
“…The basis for the discrepancy between our results and previous studies, with respect to the ability of tyrosine to be transported through the blood–brain barrier in the presence of elevated Phe, may arise from the different lengths of time the blood–brain barrier was exposed to elevated Phe levels. Previous studies administered a bolus of Phe and shortly thereafter Phe and tyrosine flux was measured in vivo into the brain or in vitro through isolated brain capillary vessels (Choi and Pardridge 1986; Brenton and Gardiner 1988; Pardridge 1998). In contrast, the untreated PKU mouse blood–brain barrier was continuously exposed to abnormal Phe and tyrosine levels from shortly after birth into adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…ment of accumulation into brain is a direct estimate of transfer from blood. On the basis of uptake studies, amino acid transport into the developing brain has generally held to be high compared with the adult (Bañ os et al, 1978;Braun et al, 1980;Brenton and Gardiner, 1988;Cornford et al, 1982), but the extent to which this is due to increased uptake as opposed to incorporation was not always clear. Lefauconnier (1992) has outlined some of the technical problems associated with study of amino acid transport in small immature animals, as well as providing a useful summary of age-related differences.…”
Section: Blood-csf Transfer Of Metabolicallymentioning
confidence: 99%
“…From this, it was concluded that there may be separate amino acid transport mechanisms that mature at different times. Later evidence has shown that amino acid transport in the developing brain is generally high compared with the adult; 61 –64 presumably this is a reflection of the rapid growth of the developing brain. Lefauconnier 65 has outlined some of the technical problems associated with the study of amino acid transport in small immature animals, as well as providing a useful summary of age‐related differences.…”
Section: Other Barrier Mechanisms In the Developing Brainmentioning
confidence: 99%